Endometriosis patients with infertility - Jefferson, Luz (2015)
To determine the incidence and characteristics of presentation of endometriosis patients with infertility. DESIGN: In a retrospective study of medical records of 2720 patients attending the Infertility Clinic of the Archbishop Loayza Hospital, between the months of January 1993 and July 1997 was revised RESULTS: Of the 532 patients underwent laparoscopy or laparotomy and 773 cases of endometriosis was found, representing 32.5%. They entered the study 166 cases that met the inclusion criteria. The age of the patients was 33.3 ± 4.9 years (mean ± standard deviation). 59% of the cases occurred in stage I of endometriosis. Most patients (59.6%) had primary infertility and infertility average time was 51.2 (± 38.4) months. 75.9% of the patients had some type of symptoms, primarily pain (dysmenorrhea, dyspareunia, chronic pelvic pain), but only 25.9% had alterations in the pelvic exam. 66% of patients had associated pathology, especially tubal. As for treatment it received 8.4% of the cases received medical treatment, surgical treatment 29. 5%; 7.8% combined treatment (medical and surgical); 38.5% expectant management. The pregnancy rate was 25%. CONCLUSION: Endometriosis was found in one third of infertile women in our study.